Exploring the potential of Block Chain Technology; a bibliometric analysis using VoSViewer - Swain, Sukhamaya; Goyat, Suman; Bhattacharya, Siddhartha; Malik, Himanshu (Journal of Neonatal Surgery, 2025)
Blockchain Technology is evolving and the applications are increasing with newer areas being touched upon. Naturally, there has been enough research through publications also happening in the same space. Thus, it is important to do a bibliometric analysis to provide an understanding of the progress till now and the available trends thereon. This study aims to explore the state of affairs, progress till now, issues & trends and the future of Blockchain Technology through a bibliometric analysis covering the period from 2015 to 2024. For the study, the researchers use Scopus database to collect relevant publications. These are further analysed through Vosviewer software. This will provide rich insights for the future researcher.